If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -3 = 2y + 15 Reorder the terms: -3 + 6y = 2y + 15 Reorder the terms: -3 + 6y = 15 + 2y Solving -3 + 6y = 15 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -3 + 6y + -2y = 15 + 2y + -2y Combine like terms: 6y + -2y = 4y -3 + 4y = 15 + 2y + -2y Combine like terms: 2y + -2y = 0 -3 + 4y = 15 + 0 -3 + 4y = 15 Add '3' to each side of the equation. -3 + 3 + 4y = 15 + 3 Combine like terms: -3 + 3 = 0 0 + 4y = 15 + 3 4y = 15 + 3 Combine like terms: 15 + 3 = 18 4y = 18 Divide each side by '4'. y = 4.5 Simplifying y = 4.5
| 2(x-2)-16=8-2x | | 13q+8=9q | | -x^5+2x^4-4x^3= | | 9x-63=4x+22 | | s+6=8(9) | | 6m+2(m+7)=m | | x-6=66-15(x+8) | | -14x+9+7x=-12 | | 4-(-2)(3)= | | x-6=66-15 | | 10e^3x-e=2e^3x | | -119=-17n | | 6+4x=3(3x+2)-x | | 2g-g-h+3h+2h-h= | | 12u-18=8u-6-1u-8 | | 3b^3-192= | | k-10-4k=10-k | | 215= | | 4-5y=(-16) | | 6+4c=3(3x+2)-x | | 3x-10-5x=-24 | | 9x-12+5x=3 | | 7=7x-3(6x+8) | | 2x+4=25x | | -9+5z=-7+9z+2 | | 8x+39=3x-1 | | 4h=3xy | | 32=f-3f+6f | | -9z+5z=-7+9z+2 | | 6(x+1.39)=5x | | 8x-26=6x-4 | | 4+3v-7v-2+v= |